Cognitive motivation and its relationship to the concept of self on middle school students (female) (Journal of the College of Education for Women, 2019)
The preparatory phase since it corresponds to adolescence are the most important stages of life , where the individual 's personality to take shape at this stage and start asking questions about the same , trying to discover the positive and negative traits hehas in order to form distinctive character and also is being he have Love Poll For everything that goes on around him.And attention to cognitive motivation is important for students because the student who owns a motive cognitively looking for self - knowledge with conviction, and learning then be meaningful and lasts long. The motive of knowledge are common in which cognitive components does not mean exclusive knowledge on academic books and research in the narrow borders but also the expansion of knowledge to include the free readings and research and investigation, and the active search for new information and gravitate towards the mysterious subjects that lack of information and the challenge to get the information.On the other hand Self - concept is a configuration hypothetical cognitive and united and educated for Perception emotional perceptions and divisions own self, Ablorh individual definition psychologically for itself, that the perceptions of the individual connected to itself and the shrouded from the provisions of Evaluative emotional and trends are essential guides to his motives and behavior and adaptability profile. And self - concept is a key stone in the construction of personal, who organizes and determines the behavior and plays a pivotal role in shaping the behavior of the individual and to highlight its own characteristics.The current research aimed at the following:Is there Relationship between Motivation Cognitive The concept Self At I Baht Phase Junior high.Reviewed by a researcher in the theoretical framework of the research variables have embraced the theory (Maslow) as the basis for the study of cognitive motivation, the theory (Rogers) to study Concept Self. In order to achieve the goals of current research , the researcher to adopt a cognitive measure of motivation (Mahmoud's (2004), which conducted a researcher Wafaa Mahmood Younis (2007) amendments on him, And also Adopted Scale Concept Self For (Dr. ZiadBarakat (2009) to be applied On a sample Of 100 students It was Selected More random From Number From Schools Directorate Rusafa Second On according toVariables (Grade And specialization).The researcher statistical procedures necessary when the adoption of sincerity, firming, and extracted the discriminatory power of the paragraphs of the two extremes measure my style and the relationship of paragraph college degree. After collecting and processing information statistically using statistical methods to the researcher found: A positive relationship between motivation and cognitive self - concept. The update of the aspects related to the current research recommended Researcher Several Recommendations Including1. Interest motivation cognitive learning to be meaningful because the student who has the motivation cognitively looking for self - knowledge with conviction.2. Work on the composition of a positive self - concept among students since it is an important factor of the factors that influence the behavior and mental health.And suggested Researcher Number From Studies Including:1. Further study on a sample of students in middle school and compare the results.2. Conduct a similar study on a sample of students in elementary and middle stages.